A NOVEL REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHIC METHOD FOR SIMULTANEOUS ESTIMATION OF ALOE-EMODIN AND PIPERINE IN AYURVEDIC FORMULATION - TANDEL, LEENA; SONONE, REVATI; JAIN, VANDANA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of this study was to develop and validate a novel, simple, rapid, accurate, and precise reverse-phase high-performance liquid chromatographic (RP-HPLC) method for simultaneous estimation of aloe-emodin and piperine in the ayurvedic formulation as per the International Conference on Harmonization guidelines. Methods: Chromatographic separation was achieved using a Prontosil C18 (250 × 4.6 mm, 5 μ), with a mobile phase consisting of 0.05% orthophosphoric acid and acetonitrile in the ratio of 50:50, at a flow rate of 1 ml/min and column temperature maintained at 28°C and ultraviolet (UV) detection at 225 nm. Results: The retention time of aloe-emodin and piperine was found to be 9.38±0.2 min and 13.45±0.2 min, respectively. The linearity of aloe-emodin and piperine was tested in the range of 1–20 μg/ml. The correlation coefficient for aloe-emodin and piperine was found to be 0.998 and 0.997, respectively. The recovery values (98–102%) indicate a satisfactory accuracy. The percentage relative standard deviation for precision was found to be <2% which indicates that the method is precise. Conclusion: A precise method for the simultaneous quantification of aloe-emodin and piperine was developed using high-performance liquid chromatography. Hence, the developed method can be used for quantitative and quality control analysis of formulations containing these phytoconstituents.